Effects of antibacterial mineral leachates on the cellular ultrastructure, morphology, and membrane integrity of Escherichia coli and methicillin-resistant Staphylococcus aureus - Otto Caitlin C; Cunningham Tanya M; Hansen Michael R; Haydel Shelley E (BMC, 2010)
Abstract Background We have previously identified two mineral mixtures, CB07 and BY07, and their respective aqueous leachates that exhibit in vitro antibacterial activity against a broad spectrum of pathogens. The present study assesses cellular ultrastructure and membrane integrity of methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli after exposure to CB07 and BY07 aqueous leachates. Methods We used scanning and transmission electron microscopy to evaluate E. coli and MRSA ultrastructure and morphology following exposure to antibacterial leachates. Additionally, we employed Baclight LIVE/DEAD staining and flow cytometry to investigate the cellular membrane as a possible target for antibacterial activity. Results Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) imaging of E. coli and MRSA revealed intact cells following exposure to antibacterial mineral leachates. TEM images of MRSA showed disruption of the cytoplasmic contents, distorted cell shape, irregular membranes, and distorted septa of dividing cells. TEM images of E. coli exposed to leachates exhibited different patterns of cytoplasmic condensation with respect to the controls and no apparent change in cell envelope structure. Although bactericidal activity of the leachates occurs more rapidly in E. coli than in MRSA, LIVE/DEAD staining demonstrated that the membrane of E. coli remains intact, while the MRSA membrane is permeabilized following exposure to the leachates. Conclusions These data suggest that the leachate antibacterial mechanism of action differs for Gram-positive and Gram-negative organisms. Upon antibacterial mineral leachate exposure, structural integrity is retained, however, compromised membrane integrity accounts for bactericidal activity in Gram-positive, but not in Gram-negative cells.